Early Polytherapy for Probably Benzodiazepine Refractory Naïve Status Epilepticus (Stage 1 Plus) - Giuseppe Magro (Neurology International)
Stage 1 Plus is defined here as a naïve, previously untreated, status epilepticus (SE) that is probably refractory to Benzodiazepines (BDZ). These cases include not only prolonged SE as previously proposed by the author (SE lasting > 10 min) but also other cases notoriously associated with BDZ refractoriness such as the absence of prominent motor phenomena and acute etiology (especially primary central nervous system etiology). Interestingly, the absence of prominent motor phenomena as is the case of non convulsive SE might implicitly fall in the category of prolonged SE due to the delay in recognition and treatment. Future studies should help identify other factors associated with BDZ refractoriness, therefore widening the definition of Stage 1 Plus. The appropriate timing for defining prolonged SE may also differ depending on different etiology. Consequently, in future tailored models of SE, the definition of prolonged SE could be enhanced by defining it for a longer duration than Tx, a time point that changes based on different etiologies (x), Tx being much shorter than 10 min in acute etiologies. These cases of naïve probably BDZ refractory SE (Stage 1 Plus) might require a different approach: combined polytherapy from the start. The objective of this review is to provide pathophysiological and pre-clinical evidence, mostly from animal studies, for the different approach of combined polytherapy from the start for those cases of SE falling in the definition of Stage 1 Plus.